2018
DOI: 10.1021/acs.jpcb.7b11649
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Experimental and Broken Symmetry Density Functional Theory Calculated Electron Paramagnetic Resonance Parameters for the Manganese Catalase Active Site in the Superoxidized MnIII/MnIV State

Abstract: Broken symmetry density functional theory has been used to calculate g-tensor, Mn,N, and O hyperfine couplings for active site models of superoxidized Mn/Mn manganese catalase both in its native and azide-inhibited form. While a good agreement is found between the calculated and experimental g-tensor and Mn hyperfine couplings for all models, the active site geometry and Mn ion oxidation state can only be readily distinguished based on a comparison of the calculated and experimentalN azide and O HFCs. This com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 60 publications
(170 reference statements)
4
4
0
Order By: Relevance
“…It is indicated that the Mn ions in 2 a are antiferromagnetically coupled, whereas the Mn ions in 2 b and 2 c are ferromagnetically coupled possibly due to the presence of the hydroxyl group. The Heisenberg exchange coupling constant J = −70.1 cm –1 in 2 a is in good agreement with the BS-DFT results of MnCat ( J = −71 cm –1 ) with a comparable Mn–Mn distance . Rose et al experimentally found that the Mn ions in complexes 2 is antiferromagnetically coupled .…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…It is indicated that the Mn ions in 2 a are antiferromagnetically coupled, whereas the Mn ions in 2 b and 2 c are ferromagnetically coupled possibly due to the presence of the hydroxyl group. The Heisenberg exchange coupling constant J = −70.1 cm –1 in 2 a is in good agreement with the BS-DFT results of MnCat ( J = −71 cm –1 ) with a comparable Mn–Mn distance . Rose et al experimentally found that the Mn ions in complexes 2 is antiferromagnetically coupled .…”
Section: Resultssupporting
confidence: 84%
“…be seen that, after the dimanganese cofactor is oxidized to the superoxidized state (Mn III -(μ-oxo) 2 -Mn IV ), the Mn1 III −Mn2 IV distance is shortened from 3.69 to 2.72 Å. The Mn1 III −Mn2 IV , Mn1 III −O1, Mn1 III −O2, Mn2 IV −O1, and Mn2 IV −O2 distances are in good agreement with the results by BS-DFT and the experimental data of the manganese catalase (MnCat) 62,63. The Mn1 III site is five-coordinated, and the Mn2 IV site is sixcoordinated.…”
supporting
confidence: 85%
See 3 more Smart Citations